Enhancing elementary learning with Webtoon-based digital comics - Nova Suci Wulandari; Susilo Tri Widodo (Research and Development in Education (RaDEn), 2024)
One innovative learned media development that could improve student learned outcomes was digital comics. Digital comics was an innovation from printed comics that accessed used the Internet network and are more efficient. This research aimed to develop and tested the feasibility of Webtoon-based digital comic media for applying Pancasila valued. Aparted from that, to found out the effectiveness of media in improved the learned outcomes of class V students during the learning process. This researched used research and development with the waterfall model according to Somerville, which had five stages. The use of the waterfall model in this research is limited to 4 stages: 1) requirements analysis; 2) design; 3) implementation; and 4) testing. The sample in this studied was 6 class V students in small class trial subjects and 23 class V students in significant class trial subjects. Data collection techniques used interviews, validation sheets, and tests. The instruments used were interview sheets, needed questionnaires, validation sheets, response questionnaires, and pretest post-test questioned (20 cognitive questions). The validation results of material and media experts showed that the media is "Very suitable" for the learning process. Teachers and students stated that the media was "Efficient" to use in the learning process. A significant difference existed between student learning outcomes before and after using Webtoon-based digital comic media (T (22) = 9.20, p < 0.05. These findings could have used to expand media distribution to a broader scale.